(untitled) (Jurnal Bahasa, 2018)
This paper describes the process of vowel nasalization in the phonology of the Malay dialect of Saribas (MDoS). Data were analysed using Halle’s feature geometry model (1995), one of the approaches in autosegmental phonology. This study was based on field work conducted in four main Malay villages in Saratok, Sarawak. Linguistic data which were obtained from ten MDoS native speakers were collected through interviews, wordlists and audio recordings. Findings reveal that the vowel nasalization rule can be used to address a phonological problem when a vowel is preceded or followed by nasal consonants in the MDoS. The findings also demonstrate that vowel nasalization occurs when nasal segments with [+nasal] feature spread their features to the adjacent vowel causing the vowel to subsequently absorb the [+nasal] feature. Vowel nasalization in MDoS occurs progressively and regressively. The [+nasal] feature also spreads as far as possible as long as there is no opaque consonant that blocks the feature from spreading. The application of feature geometry can help to explain the constraints that take place when opaque consonants obstruct the spread of the [+nasal] feature in order to adhere to the principle of Well-formedness which prohibits the crossing of association lines. Keywords: nasal consonant, vowel nasalization, nasalized vowel, feature geometry, well-formedness condition, opaque consonants, transparent consonants, Malay dialect of Saribas